AbRSA: A robust tool for antibody numbering. (11th May 2019) - Li, Lei; Chen, Shuang; Miao, Zhichao; Liu, Yang; Liu, Xu; Xiao, Zhi‐Xiong; Cao, Yang
Abstract: The remarkable progress in cancer immunotherapy in recent years has led to the heat of great development for therapeutic antibodies. Antibody numbering, which standardizes a residue index at each position of an antibody variable domain, is an important step in immunoinformatic analysis. It provides an equivalent index for the comparison of sequences or structures, which is particularly valuable for antibody modeling and engineering. However, due to the extremely high diversity of antibody sequences, antibody‐numbering tools cannot work in all cases. This article introduces a new antibody‐numbering tool named AbRSA, which integrates heuristic knowledge of region‐specific features into sequence mapping to enhance the robustness. The benchmarks demonstrate that, AbRSA exhibits robust performance in numbering sequences with diverse lengths and patterns compared with the state‐of‐the‐art tools. AbRSA offers a user‐friendly interface for antibody numbering, complementarity‐determining region delimitation, and 3D structure rendering. It is freely available athttp://cao.labshare.cn/AbRSA .